2022-RA-1356-ESGO Epithelial ovarian cancer and brain metastases: survival analysis according to the BRCA status. (20th October 2022) - Sassu, Carolina Maria; Marchetti, Claudia; Russo, Giorgia; Minucci, Angelo; Boccia, Serena Maria; Piermattei, Alessia; Mattogno, Pier Paolo; Benato, Alberto; Olivi, Alessandro; Fagotti, Anna; Scambia, Giovanni
Abstract : Introduction/Background: Metastases of epithelial ovarian cancer (OC) can involve the central nervous system (CNS), with an incidence of 1–2%. A fundamental prognostic factor for OC is the BReast CAncer genes (BRCA) mutation but there is inconsistency in literature exploring the correlations between BRCA status and BM. Methodology: Clinical and survival information of OC patients treated for BM in our Institute from 2000–2021 was retrospectively collected. Data were compared according to the BRCA status. Results: Among 94 patients, the BRCA status was known for 66, with 21 pathogenetic mutations (BRCAm, BRCA 1 and BRCA 2) and 45 wild-type genes (BRCAwt).BRCAm patients were younger when OC and BM were detected, and no differences in the time-interval between the two diagnoses were detected according to the BRCA status. Overall, patients appeared homogeneously distributed between the two groups regarding characteristics at primary diagnosis of OC and BM ( table 1 ). More frequently, the histotype was the high-grade serous (86.2%), with FIGO stage III at disease presentation (78.7%). In most cases, CNS lesions were multiple and were associated with other extracranial metastatic sites in 59 cases (29 BRCAwt vs 14 BRCAm; P 0.544). The overall survival (OS) from the diagnosis of OC was better in BRCAm group rather than BRCAwt (median OS 81 months vs 39 months; P 0.017). Similarly, from the diagnosis of BM, the survival was longer in BRCAm patients (median OS 23 months vs 11 months; P 0.033). ( figure 1 ) Conclusion: No differences in clinical characteristics of patients at the diagnosis of OC and BM were found according to the BRCA status. A prolonged survival was detected in BRCAm vs BRCAwt OC patients with BM.